Do Financial Performance and Corporate Governance Effect on Firm Value: Evidence from Manufacturing Sector - Farawansyah, Nur Indah; Rahayu, Sovi Ismawati; Zhafiraah, Nazma Riska (Research of Business and Management, 2024)
This study attempts to investigate, either partially or simultaneously, the effects of Financial Performance as determined by Profitability, Solvency, liquidity well, and Good Corporate Governance, as decided by the Audit Committee on Firm Value and the Independent Board of Commissioners. The study approach is quantitative and makes use of secondary data-manufacturing firms registered on the Indonesia Stock Exchange. The population in this study is made up of 143 manufacturing firms. In the interim, the sample for this study was chosen through the technique of purposeful sampling. The analysis method used is multiple linear regression analysis. The Kolmogrof-Smirnof test, multicollinearity test, heteroscedasticity test, t-test, and coefficient of determination test were all employed in this investigation. The study's findings demonstrate that the factors Independent Board of Commissioners, Profitability, Solvency, Liquidity, and Audit Committee each partially positively impact firm value. Managerial implications related to the influence of financial performance and good corporate governance are increased focus on financial performance, increased transparency and disclosure of information, implementation of good corporate governance practices, and risk and compliance management. The valuation of the firm is key in the transfer of business decisions, such as mergers, acquisitions, and stock offerings.